2019
DOI: 10.1002/chem.201902610
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Transient Anionic Metal Clusters in Palladium/Diene‐Catalyzed Cross‐Coupling Reactions

Abstract: Despite their considerable practical value, palladium/1,3‐diene‐catalyzed cross‐coupling reactions between Grignard reagents RMgCl and alkyl halides AlkylX remain mechanistically poorly understood. Herein, we probe the intermediates formed in these reactions by a combination of electrospray‐ionization mass spectrometry, UV/Vis spectroscopy, and NMR spectroscopy. According to our results and in line with previous hypotheses, the first step of the catalytic cycle brings about transmetalation to afford organopall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
(121 reference statements)
0
11
0
Order By: Relevance
“…The fact that the organozinc reagent BuZnCl⋅LiCl failed to afford the corresponding organopalladate(0) complex suggests that only highly reactive organometallics, such as RMgCl and RLi, are capable of transferring their organyl group to the palladium(0) center of L 3 Pd. This behavior resembles the transmetalation of palladium diene complexes, but contrasts that of typical palladium(II) complexes, whose reactivity toward organozinc compounds and even milder transmetalation reagents is well known and forms the basis of synthetically most useful transformations, for example, Negishi and Suzuki–Miyaura cross‐coupling reactions …”
Section: Discussionmentioning
confidence: 95%
“…The fact that the organozinc reagent BuZnCl⋅LiCl failed to afford the corresponding organopalladate(0) complex suggests that only highly reactive organometallics, such as RMgCl and RLi, are capable of transferring their organyl group to the palladium(0) center of L 3 Pd. This behavior resembles the transmetalation of palladium diene complexes, but contrasts that of typical palladium(II) complexes, whose reactivity toward organozinc compounds and even milder transmetalation reagents is well known and forms the basis of synthetically most useful transformations, for example, Negishi and Suzuki–Miyaura cross‐coupling reactions …”
Section: Discussionmentioning
confidence: 95%
“…The PSI flask is designed to have an inlet where inert gas (Ar or N 2 ) is introduced, and this positive pressure allows the solution in the flask to be introduced to the mass spectrometer via PEEK/PTFE tubing. 65 Reactions can be conducted at temperatures up to the boiling point of the solvent, and the PSI flask is designed in a way that contamination from the rubber septum leaching from the solvent can be avoided entirely, as seen in Figure 11. 66 PSI is straightforward to implement in any laboratory and allows continuous reaction monitoring.…”
Section: Electrospray Ionizationmentioning
confidence: 99%
“…A look into palladium/diene‐catalyzed coupling of alkyl halides and Grignard reagents revealed that anionic Pd complexes are formed, and the mononuclear species are short‐lived – mainly favouring formation of small Pd nanoclusters [80] . The real‐time MS analysis afforded direct aggregation state information as well.…”
Section: Applicationsmentioning
confidence: 99%
“…A look into palladium/diene-catalyzed coupling of alkyl halides and Grignard reagents revealed that anionic Pd complexes are formed, and the mononuclear species are shortlived -mainly favouring formation of small Pd nanoclusters. [80] The real-time MS analysis afforded direct aggregation state information as well. Additionally, the study discovered that the transmetalation step in these reactions actually precedes the oxidative addition step in the catalytic cycle.…”
Section: Applications In Catalysismentioning
confidence: 99%